Evaluating Rapid Rule-out of Acute Myocardial Infarction Using a High-Sensitivity Cardiac Troponin I Assay at Presentation. (1st May 2018) - Greenslade, Jaimi; Cho, Elizabeth; Van Hise, Christopher; Hawkins, Tracey; Parsonage, William; Ungerer, Jacobus; Tate, Jillian; Pretorius, Carel; Than, Martin; Cullen, Louise
Abstract: BACKGROUND: Low concentrations of cardiac troponin (cTn) have been recommended for rapid rule-out of acute myocardial infarction (AMI). We examined the Beckman Coulter Access high-sensitivity cardiac troponin I (hs-cTnI) assay to identify a single test threshold that can safely rule out AMI. METHODS: This analysis used stored samples collected in 2 prospective observational studies. In all, 1871 patients presenting to a tertiary emergency department with symptoms of acute coronary syndrome had blood taken for measurement of cTnI on presentation. The endpoint was type 1 myocardial infarction (T1MI). Sensitivity and negative predictive value (NPV) were calculated for hs-cTnI values below the 99th percentile. RESULTS: Ninety-eight patients had T1MI (5.2%), and 638 (34.1%) patients had an hs-cTnI <2 ng/L (limit of detection), with sensitivity of 99.0% (95% CI, 94.4%–100%) and NPV of 99.8% (95% CI, 99.1%–100%). No hs-cTnI value above a concentration of 2 ng/L achieved sensitivity of 99%. However, an NPV of 99.5% was achieved at values <6 ng/L. A cutoff <6 ng/L enabled 1475 (78.8%) patients to be ruled out on presentation with sensitivity of 93.9% (95% CI, 87.1%–97.7%). CONCLUSIONS: A single baseline cTn <2 ng/L measured with the Access hs-cTnI assay performed well for rule-out of AMI. This cutoff concentration identified 99% of patients with AMI and could reduce the number of patients requiring lengthy assessment. A cutoff of <6 ng/L yielded a high NPV but missed more cases of AMI than would be acceptable to clinicians.